OR09-4 Estrogen Sulfotransferase (EST) as a Mediator of Ischemic Acute Kidney Injury in Mice - Barbosa, Anne (J Endocr Soc, 2019)
Acute kidney injury (AKI) is characterized by a severe and sudden impairment in renal filtration function. A common feature in AKI is organ-crosstalk, which perturbs the homeostasis of distant organs. Previous studies have suggested that renal diseases may impair the expression and activity of drug metabolizing enzymes, but the mechanism has not been fully elucidated. To understand the effect of AKI on the liver, we established a mouse model of bilateral renal ischemia-reperfusion injury (IRI). Our results showed that the hepatic expression of estrogen sulfotransferase (EST) was highly induced in both sexes. Curiously, we also observed an induction of renal EST in male mice only. EST is a phase II conjugating enzyme responsible for the sulfoconjugation and deactivation of estrogens, which majorly encompass 17ß-estradiol (E2) and estrone (E1). Increasing evidence suggests that estrogens protect against ischemic AKI because of their anti-inflammatory activities. To determine the functional relevance of AKI-responsive induction of EST, we performed IRI on EST knockout (EST KO) mice of both sexes. Our results showed that the EST KO mice were protected from AKI in a gender-independent manner. Moreover, in comparison to WT mice, expression of the pro-inflammatory marker interleukin 6 (IL-6) was significantly reduced in EST KO. Therefore, we hypothesized that AKI-induced inflammatory response may have been responsible for the upregulation of hepatic EST, leading to a decreased renal estrogen levels and exacerbation of the renal injury. But to our surprise, our results showed that amongst the evaluated groups no differences were found in the levels of estrogens; neither did ovariectomy nor castration abolish the protection phenotype of EST ablation, which finally confirms estrogen and testosterone play no effect in the attenuated profile. Using an EST KO mouse strain that overexpresses hepatic EST via the tet-off system (KOLE), we further observed that upon hepatic restoration of EST the injury phenotype was reinstated in males but not in females. Additionally, transcriptome analysis of kidneys collected from WT and EST KO mice evidenced that Cyp24a1, a renal enzyme responsible for degrading the active form of vitamin D (calcitriol), was highly induced in the protected group. Other genes that may be influenced by calcitriol levels were also altered. Hence, we observed that post RIR, EST KO mice have significantly diminished inflammation and tubular injury profiles in an estrogen and androgen-independent manner, and that overexpression of hepatic EST restores the AKI phenotype in male sex only. We predict that: i) changes in calcitriol levels are responsible for the attenuated profile in EST KO mice and for the gender differences observed in the KOLE group; ii) EST may indirectly control calcitriol levels through an unknown mechanism.